The conceptual framework of readiness for change towards privatisation job in public organization - Hakimi, Halimaton Saadiah; Alafeefi, Nabeel Abdulqader Ali Abdulla; Alafeefi, Fatima Rashad Abdulrahman; Kamalrudin, Massila; Kudus, Norliah; Akmal, Suriati (Human Resource Management Academic Research Society, 2024)
Privatization remains a significant agenda item for developing and transitional countries worldwide, yet its implementation often encounters resistance from stakeholders. This paper addresses the lack of studies on the readiness for change framework within public organizations transitioning to privatization. Focusing on self-esteem, self-efficacy, communication, management support, leadership competencies, and salary considerations, this study offers an overview of factors influencing readiness for change towards privatization jobs in public organizations. By synthesizing existing literature, this paper contributes to the development of a comprehensive framework for assessing and understanding readiness for change in the context of privatization. The findings underscore the importance of addressing these factors to effectively navigate the complexities of privatization within public organizations, offering valuable insights for governmental decision-makers and policymakers.